Searching in the wrong place: Might consciousness reside in the brainstem?. (23rd March 2022) - Devor, Marshall; Koukoui, Mary; Baron, Mark
Abstract: Doubtless, the conscious brain integrates masses of information. But declaring that consciousness simply "emerges" when enough has accumulated, doesn't really explain how first person experience is implemented by neurons. Moreover, empirical observations challenge integrated information theory's (IIT) reliance on thalamo–cortical interactions as the information integrator. More likely, the cortex streams processed information to a still-enigmatic consciousness generator, one perhaps located in the brainstem.